Effect of Asbestos suspension in Spermatogenesis and Oogenesis of mice (Mus musculus L.) - المالكي سامي جبر (University of Thi-Qar Journal of Science, 2014)
This study had been designed to investigate effect of asbestos suspension in Spermatogenesis and Oogenesis in Laboratory mice. The results of is study showed a significant decreased in spermatogonia , primary spermatocyte And elongate spermatide ,with reducing in diameter of seminal tubules and thickness of Germinal mass in male of mice which treated with asbestos suspension when compare with control group which treated with normal saline . The results of the present study revealed a significant decrease in number of follicles ( small, middle , large) and thecorpora lutea in female mice which treated with asbestos suspension when compare with control group which treated with normal saline.